2007
DOI: 10.1366/000370207781540060
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Surface-Enhanced Raman Spectroscopy for the Rapid Identification of Escherichia Coli and Listeria Monocytogenes Cultures on Silver Colloidal Nanoparticles

Abstract: Surface-enhanced Raman (SERS) spectra of various batches of bacteria adsorbed on silver colloidal nanoparticles were collected to explore the potential of the SERS technique for rapid and routine identification of E. coli and L. monocytogenes cultures. Relative standard deviation (RSD) of SERS spectra from silver colloidal suspensions and ratios of SERS peaks from small molecules (K(3)PO(4)) were used to evaluate the reproducibility, stability, and binding effectiveness of citrate-reduced silver colloids over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…For instance, Raman spectra of bacteria prepared in distilled water (Fig. 5) differ from the previously published spectra of the same bacteria prepared in the growth media [6]. Despite that, the results obtained in this study are in good agreement with that measured by Luo and Lin [35].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…For instance, Raman spectra of bacteria prepared in distilled water (Fig. 5) differ from the previously published spectra of the same bacteria prepared in the growth media [6]. Despite that, the results obtained in this study are in good agreement with that measured by Luo and Lin [35].…”
Section: Discussionsupporting
confidence: 81%
“…There are many ambiguities in literature concerning assignment of vibrational spectral bands of bacteria. For instance, the spectral band at 646 cm -1 of bacterial pathogens is assigned to tyrosine skeletal vibration in [8], while in [6] it is assigned to the COO -band of amino acids or C-S stretch mode of cysteine. It is well established that in case of tyrosine water solution the most intense Raman spectral bands are located at 826, 846, 1210, and 1615 cm -1 [9].…”
Section: Sers Spectra Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…[21] The main peak at 712 cm −1 was assigned to a shifted 730 cm −1 peak, due to the influence of differences in growth conditions. The excitation wavelength used in this study is quite long (1064 nm), being far from resonance with the surface plasmons of the silver colloids.…”
Section: Introductionmentioning
confidence: 99%
“…By applying different SERS substrates, numerous groups have shown that SERS spectra of different bacterial species show different spectral features, which allows the qualitative differentiation of the species by their SERS spectra [113,117,120,124,126,[128][129][130][131][132][133][134][135][136][137][138][139][140]. The range of the investigated bacteria comprises Gram-positive as well as Gram-negative bacteria.…”
Section: Analysis Of Bulk Bacteria Samples With Sersmentioning
confidence: 99%